(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2019)
Alkylaromatic compounds such as alkylphenols are the most wide spread and efficient material due to its broad practical utilization in different arenas including antioxidants, stabilizers for fuels, lubricating oils, polymeric materials and so on. In this work, (2-phenylpropan-2-yl) m-cresol with high yield was prepared from the reaction between m-cresol and _-methylstyrene in the presence of anhydrous aluminium chloride catalyst. Plackett-Burman design was applied for screening significant variables, such as, temperature, molar ratio of m-cresol to _-methylstyrene, time of reaction and amount of catalyst etc. to determine an optimum condition for the production of (2-phenylpropan-2-yl) m-cresol. Moreover, a 23 Yates pattern factorial design was used to develop a mathematical model to predict the yield of alkylation of m-cresol with _-methylstyrene. Analyses of the results revealed that temperature, molar ratio and amount of catalyst were the main effective variables. The products were characterized by FT-IR, UV-visible and 1H NMR spectroscopy. The adequacy of the suggested model was checked up. The experimental yields exhibited good agreement with the predicted yields designed by the mathematical model. Hence, (2-phenylpropan-2-yl) m-cresol has the potential to be used as an industrially important compound in various applications. Bangladesh J. Sci. Ind. Res.54(3), 195-202, 2019